Women’s Cooperatives As A Platform For Feminist Economic Movements: Enhancing Women’s Economic Empowerment In East Lombok, Indonesia - Irfan Azim; Muhammad Riyadlul Jinan; Zikri Rakhman (ADILLA : Jurnal Ilmiah Ekonomi Syari'ah, 2026)
This study aims to analyze the role of women's cooperatives as a strategy for empowerment and economic independence through a community-based feminist economic approach in East Lombok Regency. The research employs a qualitative approach with a multi-case study design, complemented by descriptive quantitative data analysis. Data were collected through in-depth interviews, field observations, documentation, and a survey involving 120 members of women's cooperatives. The results indicate that women's cooperatives play a crucial role in enhancing women's financial inclusion by providing access to business capital, savings, and micro-enterprise development. Access to business credit increased from 32% before joining to 81% after becoming members, while routine savings ownership rose from 41% to 76%. Furthermore, the proportion of members capable of developing independent businesses increased from 29% to 64%, with average incomes rising by approximately 37% within two years. From a feminist economic perspective, these cooperatives serve as collective economic spaces that strengthen women's bargaining power within the local economic structure. These findings suggest that women's cooperatives possess significant potential as an inclusive and sustainable model for women's economic empowerment.